ETYMOLOGY OF THE CONCEPT «ECONOMIC SECURITY OF THE ENTERPRISE» - BOSA, Inna (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Modern changes in the social and economic situation have again actualized the issue of developing and implementing a strategy for ensuring economic security as a separate enterprise and entire industries. At present, this task is one of the most important state priorities. The modern market economy is characterized by sharp competition, the variability of the conditions of the external economic environment. This requires the heads of enterprises not only to constantly adjust their market strategy, but also significant efforts to form an effective strategy of economic security. Enterprises in a volatile market environment face the need to find fundamentally new approaches to ensuring their own economic security (regardless of the scope of the enterprise). The process of successful operation and economic development of Ukrainian enterprises largely depends on the effectiveness of their activities in the direction of ensuring economic security. The purpose of the article is to investigate the genesis of the concept of «economic security» and formulate the author’s definition of «economic security of an enterprise». To achieve this goal, it is necessary to disclose the content of the concepts «security» and «economic security», on the basis of which we formulate the definition of «economic security of an enterprise». Materials and methods. The implementation of the tasks was achieved through the morphological analysis of the concepts of «economic security of the enterprise». Results. The article analyzes the definitions of «economic security» proposed in the scientific literature. The definitions of «economic security of an enterprise» by different authors are analyzed. Proposed and justified the author’s definition of «economic security of the enterprise.» Directions for further scientific research in the context of the effectiveness of economic management of the enterprise are determined. Conclusions. The definition of «economic security» will allow to build an adequate model for assessing the economic security of an enterprise.